Comprehensive numerical investigation of laser powder bed fusion process conditions for bulk metallic glasses - Yang, Zerong; Markl, Matthias; Körner, Carolin (Additive Manufacturing, 2024)
The successful application of laser powder bed fusion (PBF-LB/M) for fabricating bulk metallic glass (BMG) parts heavily relies on the development of effective process strategies. An optimal process strategy for BMGs is required to go beyond manufacturing defect-free parts and address the critical aspect of minimizing crystallization. However, traditional trial-and-error experimental methods for process development are time-consuming and costly. This paper uses an in-house developed simulation software, SAMPLE2D, to systematically explore PBF-LB/M process conditions for BMGs, with the Zr-based glass-forming alloy Zr59.3Cu28.8Al10.4Nb1.5 (at.%, trade name: AMZ4, AMLOY-ZR01) as an example. We uncover that BMG crystallization during PBF-LB/M is a localized phenomenon, primarily induced by short-range in-situ heat treatment. We comprehensively explore process conditions, encompassing laser beam-related parameters (beam power, speed, diameter, and line offset), as well as powder bed-related parameters (powder layer thickness, preheating temperature, and oxygen level of AMZ4). Leveraging insights derived from the parameter study, we delve into innovative scanning strategies. Various scanning strategies are explored, including line jumping, adding waiting times, translating the scan pattern, and rotating the scan pattern. Remarkably, our findings highlight line jumping as a highly effective scanning strategy to reduce crystallization while maintaining relative density. While either layer-wise translation or non-180° rotation of the scan pattern is generally not recommended, when focusing solely on consolidation and crystallization aspects. This study not only provides an in-depth understanding of how PBF-LB/M process conditions shape the properties of BMG parts, but also offers a fresh perspective on applying PBF-LB/M technology in BMG part productio
Keywords: Bulk metallic glass; Crystallization; Laser powder bed fusion (PBF-LB/M); Process condition; Numerical simulation